2015
DOI: 10.1080/ac.70.4.3096895
|View full text |Cite
|
Sign up to set email alerts
|

Using aortic distensibility index to detect coronary stenosis

Abstract: Non-invasive assessment of aortic distensibility indices is a feasible procedure to predict significant atherosclerotic coronary artery disease. Lower values are associated with significant obstructive coronary artery disease and high coronary artery calcium score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…ADI in the present study was found to decrease with increased severity of stenosis (P< 0.0011). In concordance with our study, in [24] study, patients with significant obstructive CAD showed significantly lower ADI values.…”
Section: Fig 8 the Correlation Between Adi And Degree Of Stenosissupporting
confidence: 92%
See 3 more Smart Citations
“…ADI in the present study was found to decrease with increased severity of stenosis (P< 0.0011). In concordance with our study, in [24] study, patients with significant obstructive CAD showed significantly lower ADI values.…”
Section: Fig 8 the Correlation Between Adi And Degree Of Stenosissupporting
confidence: 92%
“…ADI in the present study was inversely correlated with the degree of stenosis (r=-0.707, P< .001). In agreement with our finding, [24] found a significant inverse correlation between aortic distensibility measured using computed tomographic angiography and severity of coronary artery disease (percent luminal stenosis) r = -0.244, P = 0.045).…”
Section: Fig 8 the Correlation Between Adi And Degree Of Stenosissupporting
confidence: 92%
See 2 more Smart Citations
“…Several noninvasive diagnostic methods have been used to measure Ao elasticity in human medicine. [11][12][13][14][15][16][17][18][19][20][21] In small animal practice, noninvasive measurement of Ao elastic properties could help clinicians differentiate between secondary or idiopathic SH and situational SH, as well as to overcome measurement difficulties caused by animal movements and tremors.…”
mentioning
confidence: 99%